Students’ Perceptions, Interests, and Motivation of Tahfîdz al-Qur’ân and Tafaqquh fî al-Dîn in Indonesia - Husni, Husni; Bisri, Hasan (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2021)
This study aims to determine the correlation between perceptions, interests, and motivations towards tahfîdz al-Qur’ân and tafaqquh fî al-dîn. The research uses a quantitative approach with correlational methods, namely descriptive research that aims to determine the magnitude of the relationship between variables. The subjects of this study were students in four Islamic boarding schools in West Kalimantan and West Java. The results showed that there was a significant positive correlation between perceptions, interests, and motivations for tahfîdz al-Qur’ân with perceptions, interests, and motivations to explore Islamic sciences. These variables are correlated with each other with the moderate correlation coefficient. Students who have high perception, interest, and motivation towards tahfîdz al-Qur’ân also have high perception, interest, and motivation to become experts in Islamic religion.